2017
DOI: 10.18410/jebmh/2017/660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Breast Cancer Screening- A Camp-Based Study Among Rural Women in North Kerala

Abstract: BACKGROUND Early diagnosis of breast cancer is of extreme significance in improving the survival rates and quality of life. Unfortunately, studies have revealed that a major proportion of women from low-income countries are still not breast aware. MATERIALS AND METHODS In this study, Clinical Breast Examination (CBE) was done. In addition, we assessed the knowledge, attitude and practice of Breast Self-Examination (BSE). A cross-sectional study with quantitative method of data collection was conducted in a vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…This is high when compared to studies done in University of Buea and Abakaliki and less compared to another study in Buea and screening study among rural women in North Kerala. 7,14,19,16 In our study, only 12.6% responded that BSE should be performed monthly which is similar to study done in Trichy and is less when compared to studies in Lagos, Ethiopia and Cameroon. 4,13,18,19 That BSE must be done 10 days after onset of menstruation by women with regular menstruation was known only to 7.8% of the respondents.…”
Section: Discussionsupporting
confidence: 78%
“…This is high when compared to studies done in University of Buea and Abakaliki and less compared to another study in Buea and screening study among rural women in North Kerala. 7,14,19,16 In our study, only 12.6% responded that BSE should be performed monthly which is similar to study done in Trichy and is less when compared to studies in Lagos, Ethiopia and Cameroon. 4,13,18,19 That BSE must be done 10 days after onset of menstruation by women with regular menstruation was known only to 7.8% of the respondents.…”
Section: Discussionsupporting
confidence: 78%
“…On completion of the full-text review, 16 studies remained for inclusion in the study, 2 33-45 of which one originated from the search of the grey literature. 37 It is important to note that two sets of studies included in this review were linked. First, the study by Chowdhury et al 2 was a pilot feasibility study for the larger study published by Ginsburg et al 2 34 Second, the study by Kohler et al 33 was a qualitative exploratory study of the larger project reported by Gutnik et al 36 38 Where do CHWs currently have a role in breast cancer early detection?…”
Section: Results Search Resultsmentioning
confidence: 99%
“…Awareness raising and education The most common role for CHWs described across 14 studies was in awareness raising and education. 2 33-40 42-45 47 Activities included CHWs conducting door-to-door home outreach visits in the community to raise awareness about breast cancer, 33 35 40 45 providing educational talks at community health centres and communal areas (such as cafés and places of worship), 33 36 38 handing out pamphlets and information leaflets, 37 showing motivational videos on mobile phones 2 34 and teaching women how to perform their own BSE. 39 43 44 47 For example, in the linked studies by Gutnik et al 36 and Kohler et al, 38 four CHWs delivered educational talks in the waiting rooms at local clinics to both men and women.…”
Section: How Are Chws Currently Deployed In Breast Cancer Early Detecmentioning
confidence: 99%
“…[27] Utilization of our existing primary healthcare infrastructure and its facilities for opportunistic screening and health awareness classes by trained nonmedical community personnel such ASHA, Anganwadi workers should be recommend for our future policies. [28] Diseases Control Priorities 3 also says that community health workers who conduct screening and detection of early-stage disease are likely to be easily welcomed. [29] This simple approach would be a promising way to reduce the burden of the disease significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[29] This simple approach would be a promising way to reduce the burden of the disease significantly. [28] It is a real time to think for the ASHA as a change agent for breast cancer.…”
Section: Introductionmentioning
confidence: 99%